Short hospital stay versus day-care Mathieu hypospadias repair - Okoro Philemon; Tsang Thomas (Wolters Kluwer Medknow Publications, 2008)
Objective: This study compared the outcome of Mathieu repair between patients who went home within 24 hours on catheter and dressing and patients who were managed in hospital for 48 hours and had their catheters and dressings removed before going home. Patients and Methods: A retrospective study of Mathieu hypospadias repair performed by the same surgeon for 11 years. Outcome measures were catheter and dressing related problems/complications. Results: Sixty five patients were included in the study; 43(66.2%) were managed in-hospital for the first 48 hours (Group A), while 22(33.8%) were managed as day-care cases (Group B). Complication rate was 6(14.0%) and 3(13.6%) respectively, with fistula rate of 2(4.7%) in Group A and 1(4.5%) in Group B. Conclusion: Day care Mathieu repair of hypospadias does not increase the occurrence of complications.